Role of Samshodhana in Psoriasis - A Case Report (AYUSHDHARA, 2022)
In Ayurveda, all dermatological conditions are grouped under broad term Kushtha which again have two divisions Mahakushtha and Kshudrakushtha on the basis of their symptoms, severity and involvement of deeper Dhatu. According to Ayurveda all the skin diseases are taken under generalized term Kushtha. Psoriasis can be correlated with Ekakushtha due to very much similarity in their symptoms. Psoriasis is a long lasting, relapsing autoimmune disease having unknown etiology which consist of well defined, slightly elevated erythematous papules or plaques with dry silvery scales over the skin. Psoralen and Ultraviolet therapy (PUVA) and corticosteroids are the only option in modern medical sciences. But prolonged use of these medications have crucial complicacies and the recurrence rate is also very high. Here, Ayurveda treatment is embarked on to provide safe and efficacious treatment for psoriasis in long run without any side effects. As Shodhana therapy is requisite in the management of all skin diseases. Vamana and Virechana Karma were selected as a treatment modality because it is the only procedure which acts upon all three Doshas and Raktadi Dushyas which are vitiated in Kushtha. Shamana treatment was also given afterwards Virechana Karma to alleviate the left over Doshas and to continue the normal state of Dhatus. A 32 year old male patient having psoriasis (Ekakusta) since 4 years came to our institute for Ayurvedic management. There was a significant relief in scaling, discoloration of skin, itching and elevated patches in the skin lesions which showed that detoxification of the body i.e., Shodhana Karma balances the aggravates Doshas in the body.